(untitled) (Revista Argentina de Cirugía, 2021)
Since the development of fast-track programs in colorectal surgery with promising results, many centers started with these programs, and improved them. These programs were applied to different organs with the same results observed in colorectal surgery. Liver resections were not excluded from enhanced recovery programs, with a significant reduction in length of hospital stay and costs. Adequate patient information and commitment, multimodal analgesia, fluid therapy and early oral intake are the most important items of these programs.